Conservative treatment of early hormone-dependent breast cancer in elderly patients (65 years and older) - A. G. Manikhas; D. S. Pasekova (Опухоли женской репродуктивной системы, 2021)
Background. Standard treatment for hormone-dependent operable breast cancer includes surgery, hormone therapy (HT), and radiation therapy and chemotherapy (when necessary). Some elderly patients do not undergo surgery because of the high risk or refuse to be operated on. In such case, the only possible option is conservative treatment with hormones (± radiotherapy).Objective: to compare progression-free survival, local relapse-free survival, and metastasis-free survival between elderly patients with hormone-dependent breast cancer receiving different treatments (surgery + HT vs HT alone).Materials and methods. This study included 60 patients with stage I–II hormone-dependent breast cancer aged 65 years and older. Thirty patients in the experimental group received HT only, while 30 patients in the control group received surgery + adjuvant HT. All patients were treated at Saint Petersburg Clinical Oncology Dispensary. Patients were followed up for 3 years.Results. During 3 years of the study, three women from the experimental group (10 %) were found to have local tumor growth despite treatment. Three patients in the control group (10 %) also had disease progression, but it was associated with the development of bone metastases.Conclusion. The conservative approach to treatment of early hormone-dependent breast cancer in elderly patients is a possible option in routine clinical practice; however, it requires the analysis of indications and identification of patients who will benefit from this approach.